The central role of microglia in major depressive disorder and its potential as a therapeutic target - Xia, Xue; Li, Kaiqing; Zou, Wei; Wang, Long (Frontiers in Behavioral Neuroscience, 2025)
Major depressive disorder (MDD) is a complex neuropsychiatric condition whose multifactorial etiology remains incompletely explained by neuron-centric and neurotransmitter hypotheses alone. This review addresses that gap by positioning microglia—the CNS’s resident immune cells—as central drivers of MDD pathogenesis. We organize current evidence around five interrelated themes: hypothalamic–pituitary–adrenal (HPA) axis dysfunction, monoaminergic and kynurenine pathway imbalances, neuroinflammatory overactivation, synaptic and white-matter integrity disruption, and gut–brain axis perturbations. In MDD, microglia shift from a surveillant resting state to either an overactivated or functionally inhibited phenotype, exacerbating pathology via aberrant cytokine release, dysregulated synaptic pruning and impaired myelin support. These changes are modulated by genetic susceptibility, sex differences, environmental stressors and microbiome alterations. We then survey translational advances—traditional and novel therapeutics that modulate microglial polarization, emerging blood- and imaging-based biomarkers, and strategies to harness microglia–oligodendrocyte cross-talk for remyelination—and highlight integrative platforms for stratifying inflammation-driven versus non-inflammatory subtypes. Our principal takeaway is that microglia represent a unifying nexus and actionable target for precision interventions tailored to individual biological profiles.